The Effect of Post-Flood Trauma on the Sleep Quality of Elderly People in Teupin Banja Village, Muara Batu District, North Aceh Regency - Linda Adriani; Zulkifli Zulkifli; Zuheri Zuheri; Rohana Rohana (International Journal of Health Engineering and Technology, 2026)
Floods are natural disasters that can have significant psychological impacts, especially on vulnerable groups such as the elderly. This study aims to determine the effect of post-flood trauma on the sleep quality of elderly people in Teupin Banja Village, Muara Batu District, North Aceh Regency. The research method used an analytical design with a cross-sectional approach with 32 elderly respondents. The results showed that the majority of respondents experienced moderate-to-severe trauma (62.5%) and poor sleep quality (65.6%). Statistical tests using Fisher's Exact test showed a p-value of 0.027 (p < 0.05). This demonstrates a significant influence between post-flood trauma and sleep quality in the elderly. Elderly people with moderate-to-severe trauma tended to experience poorer sleep quality than those with mild trauma.